2022
DOI: 10.1155/2022/5227955
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Human Muscle State with Flexible Sensors

Abstract: Analyzing human muscle states has attracted extensive attention. EMG (electromyography) pattern recognition methods based on these works have been proposed for many years. However, uncomfortable wearing and high prices make it inconvenient for motion tracking and muscle analysis by using robotic arms and inertial sensors in daily life. In this study, we propose to use smart clothes integrated with flexible sensors to collect arm motion data, estimate the kinematic information of continuous arm motion, and pred… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 73 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…The sensor can be fitted on any irregular surface, enabling accurate detection of heart rate during exerciset such as weightlifting [Figure 2(b)] (Wang et al , 2021). Chen et al demonstrated the textile-based pressure sensor which is capable of monitoring epidermal pulses and shows great potential to advance the standardization and modernization of pulse palpation in traditional Chinese medicine, as shown in Figure 2(c) (Chen et al , 2022a, 2022b).…”
Section: Classification Of Vital Signs In Wearable Sensingmentioning
confidence: 99%
“…The sensor can be fitted on any irregular surface, enabling accurate detection of heart rate during exerciset such as weightlifting [Figure 2(b)] (Wang et al , 2021). Chen et al demonstrated the textile-based pressure sensor which is capable of monitoring epidermal pulses and shows great potential to advance the standardization and modernization of pulse palpation in traditional Chinese medicine, as shown in Figure 2(c) (Chen et al , 2022a, 2022b).…”
Section: Classification Of Vital Signs In Wearable Sensingmentioning
confidence: 99%
“…The system performs feature extraction of mean work frequency, median work frequency, peak work frequency, and mean power in EMG of biceps femoris and bilateral lower extremity lateral gastrocnemius muscles, followed by classification of stroke patients and healthy adults using neural network models in machine learning algorithms with an accuracy of 80%. However, EMG or motion sensors alone are difficult to use for muscle status monitoring [ 65 ]. Park et al [ 66 ] combined EMG signals with plantar pressure signals to obtain gait, an important marker of disability, injury, and gait symmetry.…”
Section: Bioelectrical Signalsmentioning
confidence: 99%